2019
DOI: 10.1111/ijd.14550
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of advanced oxidation protein products (AOPPs) in patients with Henoch–Schonlein purpura and its relationship with aberrant glycosylation of IgA1 and Cosmc mRNA expression

Abstract: BackgroundHenoch–Schonlein purpura (HSP) is a systemic small vessel vasculitis that is mainly caused by IgA1‐type immune complex deposition. Advanced oxidation protein products (AOPPs) are specific markers of protein oxidation.ObjectiveTo explore the role of AOPPs in the pathogenesis of HSP.MethodsThere are 51 HSP patients who were divided into four subgroups: (i) skin type – 20 cases; (ii) joint type – 8 cases; (iii) abdominal type – 12 cases; (iv) renal type – 11 cases; and 18 healthy volunteers were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Our results are consistent with the study conducted by Descamps-Latscha et al [44] on 59 CKD patients, where a positive correlation between serum AOPP and CRPus levels was reported (r = 0.255, p < 0.05). Furthermore, AOPP could be involved in the pathogenesis of the micro-inflammation of chronic kidney disease by inducing increased expression of fibronectin and collagen I in mesangial cells and enhance vascular inflammation by stimulating pro-inflammatory mediators such as vascular-1 and intercellular-1 cell adhesion molecules [45,46]. Therefore, the increase of AOPP and CRPus could reflect the progression of CKD stage and the degradation of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the study conducted by Descamps-Latscha et al [44] on 59 CKD patients, where a positive correlation between serum AOPP and CRPus levels was reported (r = 0.255, p < 0.05). Furthermore, AOPP could be involved in the pathogenesis of the micro-inflammation of chronic kidney disease by inducing increased expression of fibronectin and collagen I in mesangial cells and enhance vascular inflammation by stimulating pro-inflammatory mediators such as vascular-1 and intercellular-1 cell adhesion molecules [45,46]. Therefore, the increase of AOPP and CRPus could reflect the progression of CKD stage and the degradation of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study, white N. nucifera petal extract was shown to reduce LPO of PUFAs in Charolais cattle sperm exposed to mancozeb at low doses of 0.22 and 0.44 µg/mL [12]. Moreover, on the external surface of cell membranes, most of the proteins and some of the lipids are conjugated with short chains of carbohydrates [63]. The most common results of glycoxidation are increased advanced oxidation protein products (AOPPs) and advanced glycation end products (AGEs) [66].…”
Section: Effect Of White N Nucifera Gaertn Petal Tea Extract On Oxida...mentioning
confidence: 99%
“…Cell and organelle membranes are made from a double layer of a polar hydrophilic head and a non-polar hydrophobic tail. In most mammalian cell membranes, there are both straight-chained saturated fatty acids and unsaturated fatty acids [63]. Their polyunsaturated fatty acids (PUFAs) are sensitive to oxidative stress, which is known as lipid peroxidation (LPO) [64].…”
Section: Effect Of White N Nucifera Gaertn Petal Tea Extract On Oxida...mentioning
confidence: 99%
See 1 more Smart Citation
“…These processes have been associated with the development of autoimmune and inflammatory diseases (14). Several studies have shown that NETs are involved in the development and progression of autoimmune diseases such as ANCA-associated vasculitis, rheumatoid arthritis (RA), inflammatory bowel disease and systemic lupus erythematosus (SLE) (15)(16)(17)(18). A recent study reported that MPO-DNA is significantly elevated in the circulation of patients with IgAV and positively correlates with IgA levels, which suggests that NETs are involved in the pathogenesis of IgAV (19).…”
Section: Nets Involved In the Pathogenesis Of Igavmentioning
confidence: 99%